(untitled) (Heritage, 2025)
Demands to expand the concept of an official in Serbian criminal law emerged at the end of the 19th century due to the increasing threat to certain categories of persons such as journalists, doctors, school teachers, etc. The legislator accepted certain arguments and, with the 2009 amendments, introduced the concept of ‘work of public importance’ and protected persons performing such work. The reason for writing this paper is the 2022 Supreme (Cassation) Court decision, which expanded the concept of an official to include private security officers. The aim of this research is to examine whether there is a basis for this in the regulations that are part of the Serbian legal system. The authors use dogmatic, normative, historical and comparative law methods to analyze the available literature, legal regulations and case law. Within these methods, it was concluded that private security officers cannot be officials in the criminal legislation of Serbia.